Harnessing the Power of Social Media for Educational Innovation in Ethiopia: Challenges and Opportunities - Nurvita Sari Musdiani Silalahi; Belay Sitotaw Goshu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
Social media has become a modern education, offering opportunities and challenges to enhance learning experiences. In Ethiopia, the role of social media in the educational system is gaining attention as it is a potential means for expanding access to resources, fostering collaboration, and improving communication among students, teachers, and administrators. However, social media in education also raises concerns regarding distractions, privacy issues, and unequal access to digital technologies. The purpose is to investigate the opportunities and problems related to social media use in Ethiopia's educational system. A qualitative research approach was used, employing thematic analysis of interviews accompanied by 30 teachers, 15 education administrators, and 20 student parents. The results reveal that 65% of teachers and 58% of education administrators reported positive experiences with social media for academic engagement and communication. However, 72% of teachers and 69% of parents expressed concerns about the potential for distraction and the accessibility of inappropriate content to students. The findings also showed that 81% of parents emphasized the importance of parental involvement in regulating social media use. Meanwhile, 62% of educators highlighted the need for digital literacy programs to guide responsible use. In conclusion, the study emphasizes that social media can be a powerful tool for educational innovation in Ethiopia if effectively managed. Recommendations include the development of policies, digital literacy initiatives, and active stakeholder collaboration to ensure that social media enhances rather than hinders the educational experience.